IMPLEMENTASI PENDIDIKAN KARAKTER DI SMA NEGERI KOTA JAMBI - Zhalfa, Elsa; Winanti, Winanti; Sabila, Azzahra Raysa; Syahfitri, Thelya Mulya; Imil, Wardatul (Smart Education, 2025)
Abstract: This study aims to describe the implementation of character education in several public senior high schools in Jambi City. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The results of the study indicate that character education has been systematically integrated through intracurricular, co-curricular, and extracurricular activities. Each school develops different strategies, such as religious habits, the Pancasila Student Profile (P5) project, and contextual learning that emphasizes values such as responsibility, tolerance, and nationalism. The role of teachers as role models, as well as the involvement of parents and the surrounding environment are important factors in strengthening students’ character. Despite challenges such as limited facilities, the implementation of character education has been running progressively. This study emphasizes the importance of collaboration between all parties in forming a generation with superior character, both in terms of academics and morals. Keyword: Implementation, Character Education, Jambi City Abstrak: Penelitian ini bertujuan untuk mendeskripsikan implementasi pendidikan karakter di beberapa SMA Negeri di Kota Jambi. Menggunakan pendekatan deskriptif kualitatif, data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa pendidikan karakter telah diintegrasikan secara sistematis melalui kegiatan intrakurikuler, kokurikuler, dan ekstrakurikuler. Setiap sekolah mengembangkan strategi berbeda, seperti pembiasaan religius, proyek Profil Pelajar Pancasila (P5), dan pembelajaran kontekstual yang mengedepankan nilai-nilai seperti tanggung jawab, toleransi, dan nasionalisme. Peran guru sebagai teladan, serta keterlibatan orang tua dan lingkungan sekitar menjadi faktor penting dalam penguatan karakter siswa. Meskipun terdapat tantangan seperti keterbatasan fasilitas, implementasi pendidikan karakter telah berjalan secara progresif. Penelitian ini menegaskan pentingnya kolaborasi semua pihak dalam membentuk generasi berkarakter unggul, baik dari sisi akademik maupun moral. Kata kunci: Impelementasi, Pendidikan Karakter, Kota Jambi